Combating ecosystem collapse from the tropics to the Antarctic. (25th February 2021) - Bergstrom, Dana M.; Wienecke, Barbara C.; van den Hoff, John; Hughes, Lesley; Lindenmayer, David B.; Ainsworth, Tracy D.; Baker, Christopher M.; Bland, Lucie; Bowman, David M. J. S.; Brooks, Shaun T.; Canadell, Josep G.; Constable, Andrew J.; et al.
Abstract: Globally, collapse of ecosystems—potentially irreversible change to ecosystem structure, composition and function—imperils biodiversity, human health and well‐being. We examine the current state and recent trajectories of 19 ecosystems, spanning 58° of latitude across 7.7 M km 2, from Australia's coral reefs to terrestrial Antarctica. Pressures from global climate change and regional human impacts, occurring as chronic 'presses' and/or acute 'pulses', drive ecosystem collapse. Ecosystem responses to 5–17 pressures were categorised as four collapse profiles—abrupt, smooth, stepped and fluctuating. The manifestation of widespread ecosystem collapse is a stark warning of the necessity to take action. We present a three‐step assessment and management framework (3As Pathway Awareness, Anticipation and Action ) to aid strategic and effective mitigation to alleviate further degradation to help secure our future. Abstract : Global climate pressures and regional human impacts are causing increasing collapse of ecosystems across Australia and reaching to Antarctica. Ecosystems are experiencing multiple pressures simultaneously, either chronically (e.g. increasing air temperatures) and/or as extreme, short events (e.g. storms, fires), with their deterioration exhibiting a range of patterns. Knowing these patterns can alert conservation managers to impending collapse. We provide a new framework (the 3As) to use in conservation that focuses on preventing collapse ( Awareness of ecosystem values; Anticipation of the range of pressure; Action to stop pressures), as well as guidance as to the types of conservation options available.